2016
DOI: 10.5194/amt-9-939-2016
|View full text |Cite
|
Sign up to set email alerts
|

The airborne mass spectrometer AIMS – Part 1: AIMS-H<sub>2</sub>O for UTLS water vapor measurements

Abstract: Abstract. In the upper troposphere and lower stratosphere (UTLS), the accurate quantification of low water vapor concentrations has presented a significant measurement challenge. The instrumental uncertainties are passed on to estimates of H 2 O transport, cloud formation and the role of H 2 O in the UTLS energy budget and resulting effects on surface temperatures. To address the uncertainty in UTLS H 2 O determination, the airborne mass spectrometer AIMS-H 2 O, with in-flight calibration, has been developed f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Detailed descriptions about the measurement strategy and uncertainties in the data processing are discussed in Afchine et al (2017). IWC is derived from the difference between the amount of total enhanced water (H 2 O tot ) and the amount of gas-phase water (H 2 O gas ) (Kaufmann et al, 2016). Due to the enhancement factor (Voigt et al, 2006) at the HALO-TGI, which is about 20-35, the minimum detectable IWC is in the range between 1 and 2000 ppm (1-2000 × 10 −2 mg m −3 ).…”
mentioning
confidence: 99%
“…Detailed descriptions about the measurement strategy and uncertainties in the data processing are discussed in Afchine et al (2017). IWC is derived from the difference between the amount of total enhanced water (H 2 O tot ) and the amount of gas-phase water (H 2 O gas ) (Kaufmann et al, 2016). Due to the enhancement factor (Voigt et al, 2006) at the HALO-TGI, which is about 20-35, the minimum detectable IWC is in the range between 1 and 2000 ppm (1-2000 × 10 −2 mg m −3 ).…”
mentioning
confidence: 99%
“…The Arctic polar vortex during the winter 2015/2016 has already been subject to a number of studies, most of them directly related to POLSTRACC activities. Overviews of the evolution of the polar vortex are given by Manney and Lawrence (2016), Matthias et al (2016) and Khosrawi et al (2017) including satellite, reanalysis and model perspectives. Concurrently, the authors point out the exceptional strength of the vortex due to reduced planetary wave activity, accompanied by record low temperatures and extensive denitrification, dehydration and chlorine activation.…”
Section: Activities Within the Polstracc Missionmentioning
confidence: 99%
“…This is the consequence of unresolved transport of ozone and counteracting effects from catalytic depletion and stratospheric cooling during climate change, where some transport and chemical processes may not have been implemented into the models in complete detail. In particular, Khosrawi et al (2017) have shown recently that the climate model ECHAM5/MESSy Atmospheric Chemistry (EMAC) underestimates stratospheric downward transport in the polar vortex and potentially inherits uncertainties in chlorine chemistry kinetics. The lack of observations inside the polar LMS may contribute to the enhanced uncertainty.…”
mentioning
confidence: 99%
“…As a consequence, novel concepts and instruments (e.g. Thornberry et al, 2013;Kaufmann et al, 2014;Kaufmann et al, 2016;Buchholz et al, 2017) and improved techniques for inflight (Rollins et al, 2011) and ground calibration (Meyer et al, 2015) were developed to improve the accuracy of H 2 O measurements.…”
Section: Introductionmentioning
confidence: 99%